1987
DOI: 10.1139/f87-267
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Seasonal Succession in Lake Ontario at Northshore, Midlake, and Southshore Stations in 1982, and a Comparison with 1970

Abstract: The seasonal pattern of zooplankton succession in Lake Ontario was similar at three stations along a north–south transect, with differences attributable to physical factors. Because of warming within the thermal bar zone, the spring succession at the northshore station was early relative to the midlake station, but after stratification the northshore station lagged behind due to frequent upwelling events. Thermal bar formation along the south shore was followed by downwelling throughout the summer, giving a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We have shown that the sediment record provides evidence of recent changes in the trophic state of Lake Ontario when no evidence of such change, except for a qualitative change in diatom populations (Johannsson et al 1985), has been found in other limnological investigations (Johannsson et al 1985;Lean et al 1987;Stevens and Neilson 1987;Gray 1987;Taylor et al 1987). Detecting trends in real time is complicated by interannual and shorter term variability in trophic state variables (Harris 1986) which are poorly resolved by conventional sampling.…”
Section: Conchionsmentioning
confidence: 68%
“…We have shown that the sediment record provides evidence of recent changes in the trophic state of Lake Ontario when no evidence of such change, except for a qualitative change in diatom populations (Johannsson et al 1985), has been found in other limnological investigations (Johannsson et al 1985;Lean et al 1987;Stevens and Neilson 1987;Gray 1987;Taylor et al 1987). Detecting trends in real time is complicated by interannual and shorter term variability in trophic state variables (Harris 1986) which are poorly resolved by conventional sampling.…”
Section: Conchionsmentioning
confidence: 68%
“…The dynamic nature of this aspect of the zooplankton community (Dimension 2) in comparison to the relative seasonal stability of Dimension 1 in Middleton Pond, suggests that different mechanisms are influencing these two components of the zooplankton community. The zooplankton communities of some lakes and reservoirs are thought to follow fairly well characterized patterns of successional development and these seasonal patterns may be repeatable year after year (e.g., DeMott, 1983;Kratz et al, 1987;Taylor et al, 1987;Hu & Tessier, 1995). Indeed, even when a lake undergoes a series of fish additions and removals, each of which is likely to affect the zooplankton, there exists a high degree of repeatability in how zooplankton, or groups of zooplankton, respond to changes in the level of planktivory (He et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…They attributed the control of algal biomass to the physical transport of lake water masses in lieu of nutrients when the mixing zone depth exceeds that of the euphotic zone. Taylor et al (1987) reported that Lake Ontario zooplankton measured in 1982 did not change in response to changes in nutrient loading and salmonid predators during the 1970s. To examine this discrepancy, Wolin et al (1991) collected a surficial sediment core in 1987 from the Rochester Basin (Fig.…”
Section: Main Lake Regionmentioning
confidence: 99%